Lesson Study: A Collective Concern for Students’ Learning Improvement - Suwartono, Tono; Abdulloh, Abdulloh; Khomsatun, Khomsatun (Journal of Learning Improvement and Lesson Study, 2022)
Having a teaching art for a teacher has been a compulsory nowadays. Beside the basic requirement, the mastery of the content and also good lesson instructions are needed in the classroom. The skill or competency sometimes become the problems faced by the teacher in implementing a lesson plan. By understanding the cases, the teacher has to be aware of alternatives to best classroom activities. The lesson study is suggested to be an alternative solution for implementing a lesson plan. This study aimed to show how collaborative learning from the teachers can create collective concern among the teachers. This research employed a literary study directed for providing some perspectives and evidences to prove that teacher’s competence can be developed through collaborative learning. The results of this study has indicated that the teachers are strongly encouraged to apply the lesson study in attempt to find the best way for implementing the lesson plan because it can build a learning community among teachers, overcome ineffective learning practice based on clinic stages, and be implemented at any level.